Instructional Leadership Models in Education: A Comparative Review of Practices in the Philippines and Selected Countries - Diana Mae Planteras (Tecno Scientifica Publisher, 2026)
Instructional leadership was widely recognized as a key factor in improving school effectiveness and student learning outcomes. Despite its global relevance, leadership practices differed according to governance systems, cultural contexts, and accountability structures. This study aimed to examine instructional leadership models in selected countries and determine their implications for strengthening educational leadership in the Philippines. A systematic review of international and local literature was conducted, synthesizing empirical studies and policy documents from the United States, Finland, Singapore, Australia, and the Philippines. The analysis focused on governance structures, leadership preparation, autonomy, accountability, and cultural influences. The findings revealed common dimensions across countries, including curriculum supervision, teacher professional development, and student achievement orientation. However, variations existed in levels of autonomy, leadership training systems, and accountability mechanisms. Centralized systems emphasized structured frameworks and performance monitoring, while decentralized systems promoted professional trust and shared leadership. In the Philippine context, instructional leadership was guided by national standards but constrained by administrative workload, limited autonomy, and resource challenges. Emerging trends included distributed leadership, data-informed decision-making, equity-focused practices, and the influence of global policy exchange. Instructional leadership was shaped by contextual factors and needed to be adapted to local realities. Strengthening leadership preparation, reducing administrative demands, and promoting collaborative and evidence-based practices were essential for improving learning outcomes in Philippine schools.